Plasmalogenic Lipid Analogs as Platelet-Activating Factor Antagonists: A Potential Novel Class of Anti-inflammatory Compounds - Rong, Pu; Wang, Jie-Li; Angelova, Angelina; Almsherqi, Zakaria A.; Deng, Yuru (Frontiers in Cell and Developmental Biology, 2022)
Plasmalogens and Platelet-Activating Factor (PAF) are both bioactive ether phospholipids. Whereas plasmalogens are recognized for their important antioxidant function and modulatory role in cell membrane structure and dynamics, PAF is a potent pro-inflammatory lipid mediator known to have messenger functions in cell signaling and inflammatory response. The relationship between these two types of lipids has been rarely studied in terms of their metabolic interconversion and reciprocal modulation of the pro-inflammation/anti-inflammation balance. The vinyl-ether bonded plasmalogen lipid can be a precursor of the biosynthesis of ether-bonded PAF. In this opinion paper, we suggest a potential role of plasmalogenic analogs of PAF as modulators and PAF antagonists (anti-PAF). We discuss that the metabolic interconversion of these two lipid kinds may be explored towards the development of efficient preventive and relief strategies against PAF-mediated pro-inflammation. We propose that plasmalogen analogs, acting as anti-PAF, may be considered as a new class of bioactive anti-inflammatory drugs. Despite of the scarcity of available experimental data, the competition between PAF and its natural plasmalogenic analogs for binding to the PAF receptor (PAF-R) can be proposed as a mechanistic model and potential therapeutic perspective against multiple inflammatory diseases (e.g. cardiovascular and neurodegenerative disorders, diabetes, cancers, and various manifestations in coronavirus infections such as COVID-19).